Identifying Key Parameters for Enhancing Urban Resilience in Commercial Spaces: A Comparative Study in Saida, Lebanon - Nour El Baba; Ibtihal El Bastawissi; Ayman Afify; Hiba Mohsen (Proceedings of the International Conference of Contemporary Affairs in Architecture and Urbanism-ICCAUA)
Urban resilience plays a vital role in sustaining the functionality and vitality of commercial spaces in the face of evolving socioeconomic and spatial challenges. This research investigates the key parameters that enhance urban resilience in commercial spaces, focusing on the interrelationship between spatial configuration, land use activities, and consumer perception. The study examines Saida's historic commercial street in the old city alongside two contemporary shopping malls, employing a mixed-method approach to highlight the differences in spatial and consumer experiences across these typologies. Space syntax analysis is used to assess spatial configurations, complemented by data from UN-Habitat Geoportal and field observations. The research also incorporates consumer surveys to explore perceptions and behavioural patterns. The findings reveal distinct spatial and consumer dynamics between traditional and modern commercial spaces, offering actionable insights into the urban design variables critical for enhancing urban retail resilience. These insights aim to support urban designers and planners in creating adaptable and sustainable commercial environments.